CLUSTERING APPLICATION USING ARCADIS SUSTAINABLE CITIES INDEX: POSITIONING ISTANBUL IN WORLD'S LEADING SUSTAINABLE CITIES - (:unkn) unknown (SCIBULCOM LTD, 2019)
With increasing urbanisation around the world, 4 billion people living in cities today are expected to reach up to 6.5 billion by 2050. In the meantime, this rapid increase in urbanisation will reveal the materiality of sustainability. In order to transfer the today's economic, environmental and social opportunities to future generations, sustainable solutions are applied to city managements. Sustainable city is a topic that has recently been followed by developed countries. It is sufficient to examine the investments made by these countries and their future plans in order to recognise the importance of sustainable city management. In order to evaluate cities according to sustainability criteria, Arcadis Sustainable Cities Index (SCI) ranking system is used. Arcadis ranks 100 worldwide cities according to their sustainability under 20 subheadings with 32 sub-indicators every year. The purpose of this study is to cluster and compare the sustainability of selected Arcadis cities around the world using sustainability rankings of each sub-indicator. K-means clustering algorithm is applied to identify the clusters of cities. Finally, Istanbul which has a rank 77 and sustainability of 45.9% will be compared with other cities in order to define the clear points to become a more sustainable city.
Keywords: sustainable cities; Arcadis Sustainable City Index; clustering; K-means algorithm; INDICATORS